EXPERIENCE OF APPLICATION OF STEEL 1.2746, ENIS04957 IN CUTTING KNIVES FOR CHOPPING OF THE SCRAP METAL - A. I. Rozhkov; A. V. Demin; O. M. Grudnickij; V. V. Nikolaev; A. V. Feklistov; A. N. Paytash (Литьë и металлургия)
The comparative analysis of firmness of cutting knives from various brands of steel and for chopping of different types of scrap metal is provided in the article